Topos starca i młodzieńca w dramacie Pescatori Raffaela Vivianiego w kontekście świata wartości kultury antycznej - Sterna, Marta (Collectanea Philologica, 2018)
The subject of reflection in this article are antique topoi, whose transmission and reception can be observed in contemporary Italian drama. This topic is discussed on the example of RaffaeleViviani’s play entitled Pescatori (Fishermen), in which you can distinguish the presence of two topoi: a young man and an old man. Moreover, the aim of the article is to look at these topoi in the context of the world of the value of ancient culture, the echo of which also seems to resonate in the song. Taking into account, however, that the issue of connections between the dramaturgy of the Neapolitan writer and the specific elements of the Greek tragedy is an extremely broad problem, this study is merely a delineation of this subject and an indication for further directions of research.